Antibacterial activity of Camellia sinensis versus propolis against Streptococcus mutans - Cesar Felix Cayo Rojas; Luis Adolfo Cervantes Ganoza (Editorial Ciencias Médicas, 2020)
Introduction: Green tea (Camellia sinensis) and propolis contain flavonoids which inhibit the growth, metabolism and co-aggregation of Streptococcus mutans, the main causative agent of dental caries. Objective: Evaluate the antibacterial activity in vitro of 10% and 20% green tea (Camellia sinensis) ethanolic extract versus 10% and 20% propolis ethanolic extract against the growth of Streptococcus mutans (ATCC 25175) strains. Methods: An in vitro experimental prospective longitudinal comparative study was conducted. The study universe was 90 diffusion disks and the sample was 15 disks soaked up in green tea (Camellia sinensis) or propolis at various concentrations, 0.12% aqueous chlorhexidine and distilled water. Sample size was estimated by the comparison of means formula after conducting a pilot study. The diffusion disks soaked up in the substances were placed on Mueller Hinton agar planted with Streptococcus mutans (ATCC 25175) and the width of the inhibition haloes was measured at 24 h and 48 h. Nonparametric Kruskal-Wallis comparison tests and the Wilcoxon rank test were performed. Results: The maximum width of the inhibition halo achieved by 0.12% aqueous chlorhexidine, 20% green tea (Camellia sinensis) ethanolic extract, and 20% propolis ethanolic extract at 24 h was 10.64 mm ± 0.924 mm, 6.82 mm ± 0.982 mm and 8.36 mm ± 1.286 mm, respectively. The 20% green tea (Camellia sinensis) ethanolic extract showed statistically significant differences with respect to the 20% propolis ethanolic extract, both at 24 h (p= 0.013) and at 48 h (p= 0.011). Conclusions: The 20% propolis ethanolic extract displays greater antibacterial activity against the growth of Streptococcus mutans (ATCC 25175) strains than the 10% and 20% green tea (Camellia sinensis) ethanolic extract. This activity decreases with the passing of time.